Loss of MBD2 attenuates MLL-AF9-driven leukemogenesis by suppressing the leukemic cell cycle via CDKN1C - Kuangguo Zhou (Nature Publishing Group, 2021)
Abstract Acute myeloid leukemia (AML) is a deadly cancer characterized by an expanded self-renewal capacity that is associated with the accumulation of immature myeloid cells. Emerging evidence shows that methyl-CpG-binding domain protein 2 (MBD2), a DNA methylation reader, often participates in the transcriptional silencing of hypermethylated genes in cancer cells. Nevertheless, the role of MBD2 in AML remains unclear. Herein, by using an MLL-AF9 murine model and a human AML cell line, we observed that loss of MBD2 could delay the initiation and progression of leukemia. MBD2 depletion significantly reduced the leukemia burden by decreasing the proportion of leukemic stem cells (LSCs) and inhibiting leukemia cell proliferation in serial transplantation experiments, thereby allowing leukemic blasts to transition to a more mature state reflecting normal myelopoiesis. Both gene expression analyses and bioinformatic studies revealed that MBD2 negatively modulated genes related to myeloid differentiation, and was necessary to sustain the MLL-AF9 oncogene-induced gene program. We further demonstrated that MBD2 could promote LSC cell cycle progression through epigenetic regulation of CDKN1C transcription probably by binding to its promoter region. Taken together, our data suggest that MBD2 promotes AML development and could be a therapeutic target for myeloid malignancies.